Agriculture Automation System using Machine Learning and Internet of Things - Asha K N,; Gahana N,; Shishira Gowda,; Harsha C R,; Chandana D M, (International Journal of Engineering and Management Research, 2023)
Agriculture balances both food requirement for mankind and supplies indispensable raw materials for many industries, and it is the most significant and fundamental occupation in India. The advancement in inventive farming techniques is gradually enhancing the crop yield making it more profitable and reduce irrigation wastages. This project aims at making use of evolving technology i.e., IOT and smart agriculture using automation. Monitoring environmental conditions is the major factor to improve yield of the efficient crops. The feature of this project includes development of a system which can monitor temperature, humidity and moisture content of the crops in agricultural field through sensors using Arduino board. Decision tree algorithm, an efficient machine learning algorithm is applied on the data sensed from the field in to predict results efficiently which helps in decision making regarding water supply in advance.